Crystal structures, gas storage and magnetic properties of lanthanide-organic frameworks built up from dicarboxylates, [Ln2(2, 5-pydc)2(2, 5-pipdc)(H2O)2]n (Ln = Ce, Pr, Eu) and (H2pip)n[Ln2(2, 6-pydc)4(H2O)2]n (Ln = Ce, Pr, Eu, Sm). (1st November 2022) - Ay, Burak; Yildiz, Emel; Enomoto, Masaya; Okazawa, Atsushi; Kojima, Norimichi
Graphical abstract: Adsorption/desorption isotherm of H2 at 77 K for MOFs 1, 2, 4, 5, and 7 . Abstract: We have synthesized various kinds of lanthanide complexes, [Ln2 (2, 5-pydc)2 (2, 5-pipdc)(H2 O)2 ]n (Ln = Ce (MOF 1 ), Pr (MOF 2 ), Eu (MOF 3 ); 2, 5-pydc = 2, 5-pyridinedicarboxylate, 2, 5-pipdc = 2, 5-piperazinedicarboxylate), and (H2 pip)n [Ln2 (2, 6-pydc)4 (H2 O)2 ]n (Ln = Ce (MOF 4 ), Pr (MOF 5 ), Eu (MOF 6 ), Sm (MOF 7 ); 2, 6-pydc = 2, 6-pyridinedicarboxylate, H2 pip = piperazinediium) under hydrothermal conditions. The X-ray crystallographic analysis shows that [Ln2 (2, 5-pydc)2 (2, 5-pipdc)(H2 O)2 ]n forms three-dimensional coordination network, while (H2 pip)n [Ln2 (2, 6-pydc)4 (H2 O)2 ]n forms one-dimensional coordination polymer, whose different coordination network structure is controlled by the positional isomer of pyridinedicarboxylate (2, 5-pydc, 2, 6-pydc). The magnetic properties and gas storage (H2 and CO2 ) capacities were also investigated, and among the synthesized compounds MOF 7 had the highest gas storage capacities for H2 and CO2 . From the analysis of magnetic susceptibility measurements, the Weiss constants for Ce, Pr, and Sm complexes were estimated. In the case of Pr complexes, MOF 2 and MOF 5, the magnetic susceptibility deviates from the Curie-Weiss law below 20 K and 10 K, respectively, which is the precursor phenomenon of antiferromagnetic ordering. In the case of Sm(III) complex, MOF 7, the magnetic susceptibility multiplied by temperature ( χT ) as a function of temperature between 300 K and 2 K was theoretically analyzed and the spin-orbit coupling constant ( λ ) and the energy levels of ground multiplet, 6 HJ, were determined.